2009
DOI: 10.1111/j.1438-8677.2008.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity through life history of Dioon edule Lindley (Zamiaceae, Cycadales)

Abstract: The distribution of genetic diversity and structure for three populations of Dioon edule Lindley (Zamiaceae) at Monte Oscuro (MO), El Farallón (EF) and Rancho del Niño (RN) in Veracruz, Mexico was studied using 20 allozyme loci, considering four life history classes: seeds, seedlings, juveniles and adults. The MO population is genetically less diverse than the EF and RN populations. Total and local inbreeding differ significantly between life history classes. An increment of inbreeding among all classes was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 65 publications
2
11
0
1
Order By: Relevance
“…These differences were observed despite the surrounding fragments having only been separated from the continuous patch for 10-30 years. Such a pattern has also been recorded for other tree species (FARWIG, 2008;ORTEGO et al, 2010), as well as a cycad (OCTAVIO-AGUILAR, 2009). Yet post-fragmentation cohorts do not always display higher levels of differentiation than their pre-fragmentation counterparts: a number of studies have found low levels of differentiation for both cohorts (LATOUCHE-HALLÉ, 2003;SCHWARCZ et al, 2010), sometimes still with significantly higher values for juveniles than adults (RIBEIRO et al, 2005;FIGUEROA-ESQUIVEL, 2010).…”
Section: Genetic Diversity and Differentiationsupporting
confidence: 67%
“…These differences were observed despite the surrounding fragments having only been separated from the continuous patch for 10-30 years. Such a pattern has also been recorded for other tree species (FARWIG, 2008;ORTEGO et al, 2010), as well as a cycad (OCTAVIO-AGUILAR, 2009). Yet post-fragmentation cohorts do not always display higher levels of differentiation than their pre-fragmentation counterparts: a number of studies have found low levels of differentiation for both cohorts (LATOUCHE-HALLÉ, 2003;SCHWARCZ et al, 2010), sometimes still with significantly higher values for juveniles than adults (RIBEIRO et al, 2005;FIGUEROA-ESQUIVEL, 2010).…”
Section: Genetic Diversity and Differentiationsupporting
confidence: 67%
“…Various studies have revealed that some cy- (Frett, 1987;López-Ovando and Treviño-Garza, 2008;Lázaro-Zermeño et al, 2012;Lopez-Gallego, 2013). The ability of seeds to germinate under both shade conditions indicates that D. edule seeds can germinate under the oak canopy or near the mother plant, forming a transient seed bank (seeds live in or on the soil for up to one year) (Walck et al, 2005;Octavio-Aguilar et al, 2009). High germination balances the limited seed production and its high mortality, and elevated seedling mortality may have more impact on population structure (Yáñez-Espinosa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…(Zamiaceae), although the mean f was 0.27, when looking only at adults this coefficient was always > 0.30 and in at least one of the studied populations it reached values of 0.472 for juveniles and 0.475 for adults. Also the F ‐values tend to increase with life cycle class, never being > 0.165 in seed samples (Octavio‐Aguilar, González‐Astorga & Vovides, 2009). The authors suggested that this may be attributable to an extensive mortality event and subsequent founder effects.…”
Section: Discussionmentioning
confidence: 99%